Social Interaction Of Students In The Environment Of Isi Communication Science Universitas Swadaya Gunung Jati Cirebon And Fikom Universitas Islam Bandung - Sri Wulandari; Farida Nurfalah; Rita Gani (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Social interaction, continue interaction with group friends, have a big influence on the development of thought. One's conversation can compare and knowledge with other people's knowledge. Research Purposes namely; 1). How is the communication that occurs in UGJ and Unisba Students ?; 2). What about the collaboration that happened with UGJ and Unisba Students ?; 3). What is the community like for UGJ and Unisba students ?; 4). How is the creativity that occurs in UGJ and Unisba students? 5). How is the convergence that occurs in UGJ and Unnisba students? This research uses descriptive research, with qualitative research types. The results showed that the communication that occurs in UGJ and Unisba Students 1. They communicate with friends on campus or off campus directly persona, indirect group communication using the media. Hobbies related to the world. Their conversation has the same importance as perception, understanding, and lack of insight. 2. Collaboration conducted by them discussed the work, while the other informants from UGJ students also discussed the polemic on campus, to be conveyed to the invited parties. 3. The community involved in the Student Association organization likes Himakom and is active in managing laboratories, their activities off campus because of the same hobbies and friendships. 4. Creativity that occurs has a wide association, increase knowledge, friendship, get a sense of care also to pay attention to each other. 5. The convergence that occurs adjusts to each other and they prefer the campus to be a comfortable place to support each other, support each other and respect each other.